Synthesis of allyl-cyclopropyl alcohols and allyl-1,5-hexadien-3-ols and investigation of their antibacterial and antifungal activities - Servi, S; Cansiz, A; Digrak, M; Ahmedzade, M (Council Scientific & Industrial Res, 2000)
Two different methods have been used to obtain allyl-cyclopropyl alcohols and allyl-1,5-hexadien - 3 - ols, starting with various allyl substituted chloromethyloxiranes. While allyl substitued 1,5 - hexadien - 3 - ols are formed in reactions occurring with Mg in THF, the unsaturated cyclic alcohols are also formed. However, the reaction carried out with Na in CH3OH gives only 1,5 - dien - 3 - ols. Antimicrobial activity of the synthesised compounds has been tested against 16 microorganisms. The compounds have also been screened for their antibacterial and antifungal activities against bacteria, yeasts and moulds.
Keywords: <2,3>-Wittig Rearrangement; Sigmatropic Sequences